Evolución del control constitucional en el Ecuador - Zambrano-Moran, Anthony Nicodemo; Ronquillo-Riera, Orlando Iván; Moreno-Arvelo, Pamilys Milagros (IUSTITIA SOCIALIS, 2022)
Evolución del control constitucional en el Ecuador